Review on development and performance of shape memory alloy/polyimide thin-film composites - Narayane D.; Taiwade R.V.; Sahu K. (My University, 2025)
Shape memory alloy (SMA) thin films have received great importance in the research of smart (or intelligent) materials for their utilization in micro-electromechanical systems (MEMS). It is suggested that the fabrication of SMA thin films on flexible polyimide (PI) substrates paves the way for their utility as micro-actuators and sensors in many microdevices. In this review article, the development of SMA/polyimide thin-film composites using various physical vapor deposition techniques is discussed. The actuation characteristics, the influence of actuation controlling parameters, and the life cycle behavior of these composites are also concisely discussed. Furthermore, the viability of SMA/polyimide composites in various applications is also scrutinized for their shape memory properties and performance. These composites set out to be considered in soft robotic technology, an emerging domain in the field of robotics. The successful implementation of these composite actuators in bio-inspired aquatic and aerial soft robotic systems requires the generation of high actuation force and frequency to carry the payload. In the present article, the prospect of the development of SMA/polyimide sandwich-structured composite is discussed which would possibly facilitate its deployment in soft robotic applications. © 2022 Taylor & Francis.